Influence Of Distributive, Procedural And Interactional Justice On Employee Satisfaction (Case Study In The National Parliament Of Timor-Leste) - Teresa Cardoso Gomes; I Gede Riana; Pedro Miguel Barreto Ximenes (ABM: International Journal of Administration, Business and Management, 2022)
Role and Organization The National Parliament of Timor-Leste is a sovereign body which is constitutionally established "representing all citizens of Timor-Leste, with legislative, supervisory and political decision-making powers" (Article 92 of the RDTL Constitution). The powers and competences of the National Parliament, its relationship with other sovereign organs and the state, respects the principle of separation and interdependence of powers, and the rights and duties of the Deputy are provided for in three fundamental diplomas: the Constitution of the Republic. Democratic Republic of Timor-Leste, Rules of Procedure of the National Parliament and Statutes of Deputies. The purpose of this study was to analyze and explain the effect of distributive, procedural and interactional justice on job satisfaction of the employees of the Timor-Leste National Parliament. This research is a quantitative research. The data sources in this study are primary data and secondary data. The sample used in this study were 85 employees. The sampling technique used a saturated sample, that is, all of the population was used as a sample. As for the level of explanation (level of clarity) this researcher uses an associative problem formulation. The data collection method uses a questionnaire (questionnaire) and the data analysis techniques used in this study are the classical assumption test, hypothesis testing, and multiple linear regression analysis. The results of the research conducted indicate that the composite reliability values ​​of the three variables that make up the research model are all above 0.70. This means that all the reflexive indicators that make up the research model are reliable.